Talent Identification and Development in Sports Performance - Leite, Nuno (2022)
The identification and development of talent have always been a relevant topic in sports performance. In fact, a significant body of research is available worldwide discussing this longitudinal process, the qualities that underpin elite sports performance, and how coaches can facilitate the developmental process of talented athletes. Despite the continued interest given to issues of talent identification and development, recent literature highlights the low predictive value of applied and theoretical talent identification models. Talent is the expression of a complex and multidimensional phenomenon, where, despite the existing practical recommendations, many coaches and stakeholders continue to fail to adequately value the distinction between growth, maturation, and training age. Technological resources have enabled important advances, however, this has been limited essentially to defining or validating motor skills variables or genetic markers that characterize the most talented athletes. Emerging technological resources and recent methodological advances are enabling integrated assessment and monitoring to include maturational, physiological, biomechanical, and perceptual skills while also creating optimal environments for performance and dealing with injury prevention and recovery.